Non-fullerene acceptors with hetero-dihalogenated terminals induce significant difference in single crystallography and enable binary organic solar cells with 17.5% efficiency. Issue 1 (9th December 2021) - Wang, Lai; An, Qiaoshi; Yan, Lu; Bai, Hai-Rui; Jiang, Mengyun; Mahmood, Asif; Yang, Can; Zhi, Hongfu; Wang, Jin-Liang
Abstract : A synergistic hetero-dihalogenated terminals strategy was systematically employed for the first time to enhance single-crystal packing, boosting the device performance of a Y-BO-FCl :PM6 device with a remarkable PCE of 17.52%. Abstract : Despite the dihalogenation of terminals being an effective strategy to produce efficient nonfullerene acceptor (NFA)-based organic solar cells (OSCs), hetero-dihalogenated terminals are quite difficult to prepare. Here, we synthesized, for the first time, two new hetero-dihalogenated terminals (FCl-IC and FBr-IC ) with a fluorine/chlorine or fluorine/bromine pair at one terminal and three NFAs (Y-BO-FCl, Y-BO-FBr, and Y-BO-ClBr ) with three hetero-dihalogenated terminals (FCl-IC, FBr-IC, and ClBr-IC ) using a general process for OSCs, respectively. A neat film of Y-BO-FCl presents a slightly lower energy level in comparison to those of Y-BO-FBr and Y-BO-ClBr . We, for the first time, obtained single crystals of hetero-dihalogenated NFAs. On going from Y-BO-ClBr single crystals to fluorinated acceptor single crystals, the crystal systems and intermolecular packing motifs were significantly improved. The crystallographic and theoretical analysis indicate that Y-BO-FCl exhibits the most planar molecular geometry, the shortest intermolecular packing distance and largest π–π electronic coupling among these acceptors. Moreover, PM6 :Y-BO-FCl blend films present more ordered face-on orientation crystallinity, more suitable fiber-like phase separation, higher and more balanced charge mobility, and weaker charge recombination in comparison with those of PM6 :Y-BO-FBr and PM6 :Y-BO-ClBr . As a result, a performance of up to a remarkable power conversion efficiency of 17.52% with an enhanced FF value of ca. 78% was achieved in binary Y-BO-FCl :PM6 devices compared to those of PM6 :Y-BO-FBr (16.47%) and PM6 :Y-BO-ClBr (13.61%), which to date is the highest efficiency for a hetero-halogenated NFAs-based OSC. Our investigations demonstrate that a fluorine/chlorine hetero-dihalogenated terminal represents a new and effective synergistic strategy to induce significant differences in single crystals and produce high-performance hetero-halogenated NFA-based OSCs.